The Role of Science in Society's Development - Hasan, Syarfidil Hamidil; Sari, Diva Ayu Mutiara; Sholihah, Nadyatus; Sari, Anggun Puspita; Mahmudi, Kendid; Mahardika, I Ketut (International Journal of Education, Information Technology, and Others, 2024)
Science (science) has played a fundamental role in shaping the development of modern society through various innovations and discoveries that have dramatically changed people's way of life. Advances in medicine have increased life expectancy and improved the quality of public health, while advances in information and communication technology have created a more connected and informed society. Discoveries in agriculture and industry made it possible to produce food and consumer goods on a large scale, thereby changing the economic and social structure of society. However, the impact of science on society is not limited to material and technological aspects alone. The scientific method and rational thinking that are the basis of science have shaped modern society's perspective in understanding and solving various problems. This encourages the development of a society that is more critical, objective and evidence-based in decision making. Apart from that, science has also contributed to overcoming various global challenges such as climate change, food security and public health, as well as creating new ethical and social dilemmas that society must face today.